2018
DOI: 10.1021/acs.jpcb.8b04691
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Solvated Electrons in Deep Eutectic Solvents: Efficient Capture of Presolvated Electrons by DNA Base

Abstract: The solvated electron being the simplest form of an extremely reactive intermediate is of great fundamental interest in chemistry, physics, and biology since its discovery. Recently, deep eutectic solvents (DESs) have been in focus as biodegradable and cost-effective alternative to ionic liquids (ILs) for different applications. These include areas where electron transport and transfer processes are involved. Herein, we present the first report on the existence, yield, and properties of solvated electrons in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The solvated electron has also been observed in DES, and this provides the possibility of enzyme-catalyzed reactions in DESs. 57 According to a publication by Milano et al, the photosynthetic reaction center of bacteria (Rhodobacter sphaeroides) in DESs can generate a charge-separation state and even perform its natural light cycle. 58 This discovery not only verified the good maintenance of the protein structure in DESs, but also implied that DESs possess excellent electron solvation and transport properties.…”
Section: Polarity and Aciditymentioning
confidence: 99%
See 1 more Smart Citation
“…The solvated electron has also been observed in DES, and this provides the possibility of enzyme-catalyzed reactions in DESs. 57 According to a publication by Milano et al, the photosynthetic reaction center of bacteria (Rhodobacter sphaeroides) in DESs can generate a charge-separation state and even perform its natural light cycle. 58 This discovery not only verified the good maintenance of the protein structure in DESs, but also implied that DESs possess excellent electron solvation and transport properties.…”
Section: Polarity and Aciditymentioning
confidence: 99%
“…58 This discovery not only verified the good maintenance of the protein structure in DESs, but also implied that DESs possess excellent electron solvation and transport properties. 57 When considered for electrochemical applications, fast electron transfer in DESs is a strong advantage. Different types of solvent systems are critical to energy storage density.…”
Section: Polarity and Aciditymentioning
confidence: 99%
“…As a simplest form of extremely reactive intermediate, the investigation of the solvated electron plays a prominent role in physics, chemistry, and biochemistry [7–15]. For example, Adhikari et al have reported efficient capture of presolvated electrons by DNA base [11].…”
Section: Introductionmentioning
confidence: 99%
“…As a simplest form of extremely reactive intermediate, the investigation of the solvated electron plays a prominent role in physics, chemistry, and biochemistry [7][8][9][10][11][12][13][14][15]. For example, Adhikari et al have reported efficient capture of presolvated electrons by DNA base [11]. Also, considering the charge-and electron-transfer transitions, manipulation of one or several electrons at molecular level remains a highly challenging task [6,16,17].…”
mentioning
confidence: 99%
“…[1][2][3][4][5] As the simplest form of an extremely reactive intermediate, the investigation of the solvated electron plays a prominent role in physics, chemistry, and biochemistry. [6][7][8][9][10][11][12][13][14] For example, Adhikari et al have reported efficient capture of presolvated electrons by DNA base. 10 Also, for the charge-and electron-transfer and the transitions, manipulation of one or several electrons at the molecular level remains a highly challenging task 15 considering the utmost importance in the related fields of molecular electronics, 16 artificial photosynthesis, 15,17 molecular switches, 15,18 quantum-dot cellular automata (QCA), [19][20][21] solar cells, 22 and supramolecular assemblies.…”
Section: Introductionmentioning
confidence: 99%